WORKSHOP MASSAGE BAGI PESERTA PPG PENJAS FAKULTAS ILMU OLAHRAGA UNIVERSITAS NEGERI JAKARTA - Samsudin samsudin; Sudradjat Wiradihardja (Bahasa Indonesia, 2017)
ABSTRACT: Massage Workshop for PPG Participants in the Faculty of Sports Science of Jakarta State University. The purpose of community service is: (1) Programming the importance of massage socialization for PPG participants Pengas in improving knowledge, skill and skill. (2) Improve quality for PPG participants. PASS in knowledge, skills and skills. (3) Can apply knowledge, skills and massage skills to the community. A strategic objective in achieving the objectives of the activity is the students of Teacher Professional Education (PPG) FIK Universitas Negeri Jakarta. Methods in the implementation of P2M activities include: (1) Methods of lecturing and delivery of papers: mainly concerning the delivery of theoretical material. (2) Demonstrations: Provide examples and build PPG Checkers to practice various materials. (3) Discussion: Member! opportunity for participants to ask and draft training process. The conclusion of this activity is (1) PPG Student PENJAS FIK UNJ gain knowledge, skill and skill. (2) PPG Students PENJAS FIK UNJ can apply knowledge, skills and massage skills to the community. (3) Student PPG PENJAS FIK UNJ very enthusiastic follow massage training. (4) PPG Students PENJAS FIK UNJ has a new space for additional income through massage services. ABSTRAK: Workshop Massage Bagi Peserta PPG Penjas Fakultas ilmu olahraga Universitas Negeri Jakarta. Tujuan pengabdian pada masyarakat ini adalah: (1) Memprogramkan pentingnya sosialisasi massage bagi peserta PPG Penjas dalam peningkatan pengetahuan, kemampuan dan keterampilan. (2) Meningkatkan kualitas bagi peserta PPG Penjas dalam pengetahuan, kemampuan dan keterampilan. (3) Dapat mengaplikasikan pengetahuan, kemampuan dan keterampilan massage kepada masyarakat. Sasaran yang strategis dalam upaya mencapai tujuan kegiatan adalah mahasiswa Pendidikan Profesi Guru (PPG) FIK Universitas Negeri Jakarta. Metode dalam pelaksanaan kegiatan P2M meliputi: (1) Metode ceramah dan penyampaian makalah: terutama menyangkut penyampaian materi yang sifatnya teoretik. (2) Demonstrasi: Memberikan contoh dan membina peserta PPG Penjas untuk mempraktekkan berbagai macam materi. (3) Diskusi: Member! kesempatan bagi peserta untuk bertanya dam proses pelatihan. Kesimpulan dari kegiatan ini adalah (1) Mahasiswa PPG PENJAS FIK UNJ bertambah pengetahuan, kemampuan dan keterampilan. (2) Mahasiswa PPG PENJAS FIK UNJ dapat mengaplikasikan pengetahuan, kemampuan dan keterampilan massage kepada masyarakat. (3) Mahasiswa PPG PENJAS FIK UNJ sangat antusias mengikuti pelatihan massage. (4) Mahasiswa PPG PENJAS FIK UNJ memiliki ruang baru untuk penghasilan tambahan melalui jasa massage.